A review on sub-cooling in vapor compression refrigeration cycle for energy saving - Sumeru, Kasni; Sukri, Mohamad Firdaus; Falahuddin, Muhamad Anda; Setyawan, Andriyanto (Penerbit UTM Press, 2019)
Vapor compression refrigeration cycle (VCRC) is widely used in refrigeration and air conditioning (R&A) systems. Sub-cooling is used to improve the coefficient of performance (COP) of the R&A system by enhancing the cooling capacity. This paper presents various sub-cooling methods, which have been established and applied to enhance the performance of the VCRC. In a simple cycle of VCRC, the exit of the condenser is at saturated liquid line. Further cooling of the exit condenser to the sub-cooled region can result in an increase in the cooling capacity due to low vapor quality refrigerant entering the evaporator. As a result, the refrigerant absorbs more heat in the evaporator. The lower the quality of the refrigerant entering the evaporator, the higher the cooling capacity that is produced by the evaporator. This cooling capacity improvement results in an increase in the COP. In the present study, four subcooling methods are reviewed, which are liquid-suction heat exchanger, dedicated mechanical sub-cooling, integrated mechanical sub-cooling and condensate assisted sub-cooling. The advantages and drawbacks of each method, as well as future research direction in this research domain were discussed in detail